1993
DOI: 10.1111/j.1365-2133.1993.tb03312.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β distribution in basal cell carcinomas: relationship to proliferation index

Abstract: Transforming growth factor-beta (TGF-beta) distribution in basal cell carcinomas (BCCs) was studied using polyclonal antibodies recognizing intra- (precursor) and extracellular (activated) forms (LC 1-30 and CC 1-30), and compared with an index of cell proliferation (PCNA immunoreactivity). Intracellular TGF-beta is found in suprabasal keratinocytes and the outer root sheath. Extracellular TGF-beta is largely absent from normal skin, but is abundant in the intracellular spaces of hyperplastic epidermis overlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
3
29
0
1
Order By: Relevance
“…In addition, some of these cases also showed reduced E-CD expression. This is in line with previous observations showing several biological abnormalities, such as increased proliferative activity and abnormal expression of keratins, involucrin, transforming growth factor beta and epidermal growth factor receptor, in the epidermis adjacent to BCC (Said et al, 1984;Asada et al, 1993;Kikuchi et al, 1993;Stamp et al, 1993). It has been suggested that diffusible factors elaborated by malignant cells and/or activated dermal cells could interfere with the normal differentiation of adjacent normal cells, causing altered expression of several antigens in non-neoplastic keratinocytes adjacent to tumours (Wolf and Bystryn, 1981).…”
Section: P-and E-cadherin In Bccsupporting
confidence: 80%
“…In addition, some of these cases also showed reduced E-CD expression. This is in line with previous observations showing several biological abnormalities, such as increased proliferative activity and abnormal expression of keratins, involucrin, transforming growth factor beta and epidermal growth factor receptor, in the epidermis adjacent to BCC (Said et al, 1984;Asada et al, 1993;Kikuchi et al, 1993;Stamp et al, 1993). It has been suggested that diffusible factors elaborated by malignant cells and/or activated dermal cells could interfere with the normal differentiation of adjacent normal cells, causing altered expression of several antigens in non-neoplastic keratinocytes adjacent to tumours (Wolf and Bystryn, 1981).…”
Section: P-and E-cadherin In Bccsupporting
confidence: 80%
“…These results suggest that TGF-pI produced by stromal fibro blasts can act as a promoting stimulus for tumor growth and epidermal hyperplasia. This is supported by immunohistochemical observations that show elevated levels of stromal TGF-pi in hyperplastic conditions of the nor mal epidermis Kane et al 1990Kane et al , 1991FowHs et al 1992;Escherick et al 1993), as well as human and experimentally induced animal tumors Gomm et al 1991;Fowlis et al 1992;Stamp et al 1993;Zenklusen et al 1994). In addi tion, the ability of TGF-^l to affect tumor cell growth indirectly through actions on the stroma has been in ferred from studies in which the growth of subcutaneously injected malignant cell lines is enhanced when they express high levels of a transfected TGF-pi gene Steiner and Barrack 1992;Chang et al 1993).…”
Section: Discussionmentioning
confidence: 82%
“…Because human basal cell carcinomas (Stamp et al 1993), squamous carcinomas of the hamster oral epithe lium (Zenklusen et al 1994), and some human breast and colon cancers (Mizukami et al 1990;Gorsch et al 1992;Mizoi et al 1993) tissues as well as application to other cell types in which independence from negative regulation by TGF-pi is achieved by alternative mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal foreskin keratinocytes, rather than HaCAT cells, were used in the latter study, and it is not clear whether or not their cultures were confluent. TGF-t^l is a pleitropic cytokine constitutively synthesized by keratinocytes, which is present in the intercellular space of lesional psoriatic epidermis [17], in epidermis overlying basal cell carcinomas [18] and in retinoid treated epidermis [19]. TGF-;:* inhibits keratinocyte proliferation [20], and has a range of immunosuppressive actions, including: inhibition of T cell, B cell and monocyte proliferation and effector function [21.22]; inhibition of antigen presentation by cultured but not fresh Langerhans cells [23]; and reduction in dermal microvascular endothelial cell adhesiveness for peripheral blood mononuclear cells (PBMC) [24].…”
Section: Regulation Of Il-la and Il-iramentioning
confidence: 99%